Prevalence of amblyopia and refractive errors among primary school children - Rajavi, Zhale; Sabbaghi, Hamideh; Baghini, AhmadShojaei; Yaseri, Mehdi; Moein, Hamidreza; Akbarian, Shadi; Behradfar, Narges; Hosseini, Simin; Rabei, HosseinMohammad; Sheibani, Kourosh (Journal of ophthalmic & vision research, 2015)
To determine the prevalence of amblyopia and refractive errors among 7 to 12-year-old primary school children in Tehran, Iran. This population-based cross-sectional study included 2,410 randomly selected students. Visual acuity was tested using an E-chart on Yang vision tester. Refractive errors were measured by photorefractometry and cycloautorefraction. Strabismus was checked using cover test. Direct ophthalmoscopy was used to assess the anterior segment, lens opacities, red reflex and fundus. Functional amblyopia was defined as best corrected visual acuity ≤20/40 in one or both eyes with no anatomical problems. Amblyopia was present in 2.3% (95% CI: 1.8% to 2.9%) of participants with no difference between the genders. Amblyopic subjects were significantly younger than non-amblyopic children (P=0.004). Overall, 15.9% of hyperopic and 5.9% of myopic cases had amblyopia. The prevalence of hyperopia ≥+2.00D, myopia ≤-0.50D, astigmatism ≥0.75D, and anisometropia (≥1.00D) was 3.5%, 4.9%, 22.6%, and 3.9%, respectively. With increasing age, the prevalence of myopia increased (P<0.001), that of hyperopia decreased (P=0.007), but astigmatism showed no change. Strabismus was found in 2.3% of cases. Strabismus (OR=17.9) and refractive errors, especially anisometropia (OR=12.87) and hyperopia (OR=11.87), were important amblyogenic risk factors. The high prevalence of amblyopia in our subjects in comparison to developed countries reveals the necessity of timely and sensitive screening methods. Due to the high prevalence of amblyopia among children with refractive errors, particularly high hyperopia and anisometropia, provision of glasses should be specifically attended by parents and supported by the Ministry of Health and insurance organizations.